THE INFLUENCE OF THE SMART BOARD MEDIA BASED RME APPROACH ON LEARNING OUTCOMES IN THE MATERIAL ADMINISTRATION OF CLASS I PRIMARY SCHOOL - Wahyuni, Ms. Tri; Disurya, Mr. Ramanata; Imansyah, Mr. Farizal (Jurnal Tunas Pendidikan, 2025)
ABSTRACT This research is an understanding of mathematical concepts in learning. The formulation of the problem is whether there is an influence of the RME approach based on smart board media on learning outcomes in grade 1 elementary school addition material. The aim of this research is to determine the effect of the RME approach based on smart board media on learning outcomes in grade I elementary school addition material. This research method uses True Experimental design. The research subjects consisted of two class groups, namely class 1.A and class 1.B with a total of 41 students. Data collection techniques are carried out through test techniques and documentation. Data analysis techniques were carried out using normality tests, homogeneity tests, and hypothesis tests. Hypothesis testing uses the independent sample t-test. This research shows that the results of the RME approach based on smart board media have a significant effect on learning outcomes in grade I elementary school addition material. This can be seen from the results of the hypothesis using the t-test on two groups with the results obtained tcount = 4.136, while ttable is 1.684. Thus tcount > ttable (4.136 > 1.684) which means the working hypothesis (Ha) in this study is accepted, this proves that there is a significant influence of the RME approach based on smart board media on learning outcomes in class I addition material at SD Negeri 09 Sumber Marga Telang.